1996
DOI: 10.1093/ajcn/64.6.866
|View full text |Cite
|
Sign up to set email alerts
|

A double-blind crossover study in moderately hypercholesterolemic men that compared the effect of aged garlic extract and placebo administration on blood lipids

Abstract: A double-blind crossover study comparing the effect of aged garlic extract with a placebo on blood lipids was performed in a group of 41 moderately hypercholesterolemic men [cholesterol concentrations 5.7-7.5 mmol/L (220-290 mg/dL)]. After a 4-wk baseline period, during which the subjects were advised to adhere to a National Cholesterol Education Program Step I diet, they were started on 7.2 g aged garlic extract per day or an equivalent amount of placebo as a dietary supplement for a period of 6 mo, then swit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
114
1
6

Year Published

1998
1998
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 240 publications
(127 citation statements)
references
References 8 publications
4
114
1
6
Order By: Relevance
“…23 Steiner et al in a double-blind crossover study in 1996 when compared the effect of aged garlic extract with placebo on 41 men, demonstrated a 5.5% decrease in systolic blood pressure and a modest reduction of diastolic blood pressure in response to AGE. 24 This finding is similar to those in the present study that demonstrated a significant reduction of SBP whereas a modest reduction of DBP in group taking AGE along with amlodipine. Similarly, Qidwai and Ashfaq in their meta-analysis including 6 studies on 341 patients of hypertension have documented significant beneficial effects of AGE on BP of hypertensive patients.…”
Section: Blood Pressuresupporting
confidence: 92%
“…23 Steiner et al in a double-blind crossover study in 1996 when compared the effect of aged garlic extract with placebo on 41 men, demonstrated a 5.5% decrease in systolic blood pressure and a modest reduction of diastolic blood pressure in response to AGE. 24 This finding is similar to those in the present study that demonstrated a significant reduction of SBP whereas a modest reduction of DBP in group taking AGE along with amlodipine. Similarly, Qidwai and Ashfaq in their meta-analysis including 6 studies on 341 patients of hypertension have documented significant beneficial effects of AGE on BP of hypertensive patients.…”
Section: Blood Pressuresupporting
confidence: 92%
“…Garlic is known in history as treatment for cold, cough and asthma and is reported to strengthen immune system (Lawrence and Lawrence, 2011). It has many medicinal effects such as lowering of blood cholesterol level (Yeh and Yeh, 1994), antiplatelet aggregation (Steiner et al, 1996), anti-inflammatory activity (Baek et al, 2001) and inhibition of cholesterol synthesis (Piscitelli et al, 2002). Garlic has been long known to have antibacterial (Rees et al, 1993;Sasaki et al, 1999;Shobana et al, 2009), antifungal (Pai and Platt, 1995), anticancer (Unnikrishnan and Kuttan, 1990;Kaschula et al, 2010), antioxidant (Galano and Francisco-Marquez, 2009) and antiviral (Weber et al, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…In animal experiments, garlic extracts have been shown to lower plasma lipid and cholesterol in rats (Chi, 1982;Mathew et al, 1996), rabbits (Bordia and Verma, 1980) and chickens (Qureshi et al, 1983a,b). Moreover, a number of intervention studies have similarly shown that garlic and garlic preparations significantly reduced plasma lipids, especially total cholesterol and low density lipoprotein (LDL) cholesterol in humans (Jain et al, 1993;Steiner et al, 1996). However, recent studies suggested that not all garlic preparations may be hypocholesterolaemic (Simon et al, 1995;Isaacsohn et al, 1998;McCrindle et al, 1998).…”
mentioning
confidence: 99%